Trends in maternal health in Lithuania 1995–2014 - Drąsutienė, Gražina Stanislava; Drazdienė, Nijolė; Arlauskienė, Audronė; Ramašauskaitė, Diana; Zakarevičienė, Jolita; Kazėnaitė, Edita; Basys, Vytautas; Drąsutis, Jonas; Sakalauskaitė, Indrė; Sniečkuvienė, Vilija (Acta medica Lituanica, 2016)
Background. The  Lithuanian Perinatology Program, orders issued by the Ministry of Health, regulating the care and treatment of mothers and their infants, and the well-running perinatal care system helped to improve the diagnostics and treatment of pregnancy pathology. Over the last 20 years, Lithuania has experienced significant improvements in the maternal and perinatal health. Materials and methods. Data was collected from the  official statistics database, Medical Data of Births, provided by the Institute of Hygiene Health Information Centre, Vilnius University Faculty of Medicine, and the Vilnius University Centre of Neonatology in 1995–2014. Results. The  average maternal age at delivery ranged from 25.8 years in 1995 to 28.8 years in 2014. The comparison of 2001 and 2014 data shows that the incidence of gestational diabetes increased by 6.7 times due to the improved diagnosis. The percentage of hypertensive disorders decreased from 6.1% in 1997 to 3.2% in 2014. Between 1995 and 2014, the prevalence of anemia among pregnant women declined by half. The  marked decrease in respiratory, urinary, genital and other diseases was observed among pregnant women. From 1995 to 2014, in Lithuania there were 67 maternal deaths related to pregnancy and childbirth. Hemorrhage and infections during pregnancy, delivery and the postpartum period are considered the most common causes of maternal death.
Keywords: Lithuanian perinatology centres; maternal morbidity and mortality